IMPLEMENTASI PEMBELAJARAN TAHSIN TAHFIZ DALAM MENINGKATKAN HAFALAN AL-QUR`AN DI MATQ SUNANUL MUHTADIN SIDAYU GRESIK - Nashoiha, Isyroqotun (Darajat: Jurnal Pendidikan Agama Islam, 2025)
MATQ (Madrasah Aliyah Takhassus Al-Qur’an) is an educational unit under the Al-Qur’an Sunanul Muhtadin Foundation that focuses on modern, Al-Qur’an–based education integrated with scientific knowledge. In the learning process, all students are required to memorize the Qur’an as part of the institution’s vision and mission to produce excellent and Qur’ani generations. However, in its implementation, several students still face difficulties in reading the Qur’an properly and correctly according to the standards of tahsin Al-Qur’an. Therefore, a specialized method is needed to optimize tahsin and tahfiz in order to achieve high-quality Qur’anic recitation. This study aims to identify the methods and strategies used in the tahfiz learning process. It is categorized as field research, conducted directly through observation, interviews, and documentation. The implementation of tahfiz learning to improve Qur’anic memorization at MATQ Sunanul Muhtadin Sidayu Gresik has made a positive contribution to the Qur’anic learning process. These contributions include grouping students based on their tahsin quality, providing the Ummi method as a learning guide for students whose recitation still requires improvement, and allowing students with good recitation quality to memorize and add new verses daily. This classification system significantly assists tahfiz teachers in organizing and supporting students according to their respective abilities.